Turn-Taking Strategy During Video Conference Learning to Boost Student’s Confidence to Speak English: What Are High School Students’ Voices? - Ahmad Amin Dalimunte; Ilham Harahap (PT ARRUS Intelektual Indonesia, 2023)
Turn-taking strategy is considered as an important strategy in online learning, especially when the learning is utilizing zoom application. The main objective of this study was to explore students’ perceptions of using turn-taking strategy using during the video conferencing to boost students’ confidence in speaking English. The study involved ten Islamic high school students in Medan. They were selected purposively to be interviewed. Following Miles and Huberman (2014), the data analysis procedure involved data reduction, data display, and drawing conclusions. The results of the study showed that teacher regarded his students’ confidence increased during the learning through video conference. The results also revealed that the students also feel the same way as the teacher does. This happened because of lack of anxiety which can be seen by the way students behave when they were in zoom video conference. The findings implied that turn-taking strategy can be regarded as one appropriate strategy to be used during online learning through video conference application to help students’ confidence in speaking English.